Controllable HTHP sintering and property of cBN/diamond composites containing Ti3SiC2. Issue 9 (15th June 2020) - Ji, Huanli; Liang, Yuxin; Jiang, Ziling; Li, Zhihong; Zhu, Yumei
Abstract: In the study, cubic boron nitride (cBN)-diamond composites with Ti3 SiC2 (TSC) additive were prepared by high temperature and high pressure (HTHP) process. Effects of TSC decomposition on the properties of composites were systematically evaluated. Remarkable enhancement of cBN composites was achieved by controlling TSC decomposition and taking the advantage of lamellar structure of TSC. First, chemical reactions between partial decomposition products of TSC and cBN/diamond grains produced covalent bonds in composites. Second, the deformation and filling of Ti3 SiC2 as secondary phase strengthened and toughened the materials. Hence, the performance of Ti3 SiC2 -modified composites was significantly improved. Ti3 SiC2 -doped cBN/diamond composite prepared at 1500 °C exhibited the highest bending strength of 678 MPa. At 1550 °C, cBN/diamond composite containing Ti3 SiC2 showed high densification (>99 %) and the highest hardness (62 GPa) and fracture toughness (7.3 MPa m 1/2 ). High performance of cBN/diamond composite paves the way for its application as cutting inserts. Graphical abstract: Image 1